Waveguide channel for TNK linear accelerator–injector - Chernov, K.N.; Makarov, I.G.; Matyash, N.V.; Melekhova, R.I.; Ostreiko, G.N.; Persov, B.Z.; Ruvinsky, S.I.; Serdobintsev, G.V. (Вопросы атомной науки и техники, 2004)
80 MeV linear accelerator is a part of the industrial storage facility at the State Research Institute for Problems in Physics named after F.V. Lukin (Moscow, Zelenograd). 6-meter long accelerating DAW structure operates at 2.8 GHz and is powered by the Olivin klystron station. The power is transmitted through the long waveguide channel made of rectangular copper pipes with 90·45 mm cross section and 5 mm walls, with no circulator. The paper deals with the waveguide channel construction features, including indium gaskets to connect individual parts. The waveguide channel length correction procedure for the purpose of overvoltage decreasing during accelerating structure breakdowns is also described.